Key health outcomes for children and young people with neurodisability: qualitative research with young people and parents. Issue 4 (19th April 2014) - Allard, Amanda; Fellowes, Andrew; Shilling, Valerie; Janssens, Astrid; Beresford, Bryony; Morris, Christopher
Abstract : Objectives: To identify key health outcomes, beyond morbidity and mortality, regarded as important in children and young people with neurodisability, and their parents. Design: Qualitative research incorporating a thematic analysis of the data supported by the Framework Approach; the International Classification of Functioning, Disability and Health (ICF) provided a theoretical foundation. Setting: The study was conducted in community settings. Participants: Participants were 54 children and young people with neurodisability: 50 participated in focus groups, and 4 in interviews; 53 parents participated: 47 in focus groups and 6 in interviews. Children/young people and parents were recruited through different networks, and were not related. Results: Children/young people and parents viewed health outcomes as inter-related. Achievement in some outcomes appeared valued to the extent that it enabled or supported more valued domains of health. Health outcomes prioritised by both young people and parents were: communication, mobility, pain, self-care, temperament, interpersonal relationships and interactions, community and social life, emotional well-being and gaining independence/future aspirations. Parents also highlighted their child's sleep, behaviour and/or safety. Conclusions: Those responsible for health services for children/young people with neurodisability should take account of the aspects of health identified by families. The aspects of health identified in this study provide a basis for selecting appropriate health indicators and outcome measures.